2007
DOI: 10.1021/ct600240y
|View full text |Cite
|
Sign up to set email alerts
|

QM/MM Minimum Free-Energy Path:  Methodology and Application to Triosephosphate Isomerase

Abstract: Structural and energetic changes are two important characteristic properties of a chemical reaction process. In the condensed phase, studying these two properties is very challenging because of the great computational cost associated with the quantum mechanical calculations and phase space sampling. Although the combined quantum mechanics/molecular mechanics (QM/MM) approach significantly reduces the amount of the quantum mechanical calculations and facilitates the simulation of solution phase and enzyme catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
200
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(203 citation statements)
references
References 92 publications
2
200
0
1
Order By: Relevance
“…Yet, one approach to accomplish this goal is through stepwise free energy calculation with the QM/MM/molecular dynamics implementations, such as QM/ MM-FE (free energy) (13) and QM/MM-MFEP (minimum free energy path) (14). However, such calculations would be highly time-consuming.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, one approach to accomplish this goal is through stepwise free energy calculation with the QM/MM/molecular dynamics implementations, such as QM/ MM-FE (free energy) (13) and QM/MM-MFEP (minimum free energy path) (14). However, such calculations would be highly time-consuming.…”
Section: Resultsmentioning
confidence: 99%
“…The approximate QM/MM total energy becomes (9) It has been shown that this linear-polarization QM ESP charge model yields quite accurate energetics for reaction systems, given a good initial reference state [81,61]. It is even possible to further simplify this QM ESP charge model by truncating the polarization effects of the QM ESP charges [61,62].…”
Section: Reaction Path Potential Based On Ab Initio Qm/mm Methodsmentioning
confidence: 99%
“…Beyond this distance, the MM point charges merely contribute by providing a static electrostatic potential. Therefore a simple technical scheme has been adopted in our simulations with periodic boundary condition [61,62,60] in which a cutoff of 9 ~ 14 Å was used for selecting MM charges for the QM SCF calculation. The QM calculation yielded polarized QM ESP charges that were in turn used to represent the QM subsystem during MD simulations with the long range electrostatic interactions treated by the Particle-mesh Ewald Method [63].…”
Section: Long-range Qm/mm Electrostatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, we used the QM/MM-free energy ͑QM/MM-FE͒ method 58 that has a good record in the previous studies of solution-phase and enzyme-catalyzed reactions. 59 In the first step, a gas-phase geometry optimization of KMG-20 without the bound Mg 2+ ion was performed using DFT with the B3LYP functional. Next, this structure was solvated in a 20 Å sphere of classical MM water molecules described by the TIP3P model, 60 and a QM/MM-FE optimization was carried out.…”
Section: Computational Detailsmentioning
confidence: 99%